Música religiosa e afetos : um estudo de caso a partir da obra sacra do padre Chromácio Leão. - Silva, Antônio Petrônio da (2021)
Art plays a relevant role in human relationships, whether in the way of life, through the social legacy, in the way of thinking and acting, in the set of standardized guidelines, as a mechanism for the normative regulation of behavior. Since music is an integral part of this process, it is necessary to know the relationships and functions it occupies in a given context to reveal the role and meaning it brings to culture. It is also important for the Sciences of Religion, from the moment it presents in the field of investigation, relevant information about religious interrelations. Thus, the study sought to know the meaning of the musical work of Father Chromácio Leão in its historical and cultural context (1912-1951), in particular, to music of a religious genre. In this sense, from a perspective in which music performs functions, arouses feelings and represents religious symbologies, the analyzes carried out took place. Thus, it was necessary to know since the beginnings of Christian music, learn about guidelines and norms of the Catholic Church, obtain information about the theory of affections, aesthetics and musical techniques. In addition, the interrelationships between music and religion were presented, punctuating genres, styles, forms and symbologies inherent to the process of musical dialogue in the Catholic Church. religious music in Brazil. Finally, with the analysis of selected music scores, information and nuances were captured, confronting them with the current of the doctrine of affections, descriptive music, aesthetic foundations and information on functional harmony. And these brought answers to the objectives of this research. Renowned authors such as Candé (1994), Grout and Palisca (1994) and Palen ([1958]) were used as theoretical references in the field of Music History; in the relationship between music and religion in the Catholic Church in Brazil, we worked with researchers and historians such as Croato (2010), Tinhorão (2010), Kiefer (1976), Diniz (1971) and Andrade (2015). In parallel, theorists and scholars of the Doctrine of Affections, among which are Mattheson (1681-1764), Rameau (1683-1764), Quantz (1679-1773) and Charpentier (1643-1704); of musical aesthetics, Koellreutter (1984); of functional harmony Chediack (1986), Kostka and Payne (2020) and Almada (2012), were used as methodological tools in the analysis of the studied religious musical works.